Prenatal Ethanol Exposure Misregulates Genes Involved in Iron Homeostasis Promoting a Maladaptation of Iron Dependent Hippocampal Synaptic Transmission and Plasticity - De La Fuente-Ortega, Erwin; Plaza-Briceño, Wladimir; Vargas-Robert, Sofía; Haeger, Paola (Frontiers in Pharmacology, 2019)
Prenatal ethanol exposure (PAE) induces behavioral maladptations in offspring, including a deficit in memory formation which is part of the umbrella sign of Fetal Alcohol spectrum disorder. Clinical and preclinical studies have shown that iron depletion exacerbates cognitive problems in offspring exposed to ethanol in utero and that PAE promotes dysregulation in brain iron homeostasis. However, the mechanisms underlying brain iron dysregulation and neuronal activity defects in adolescent offspring of PAE are unclear and poorly understand. Here, we used a PAE rat model to analyze mRNA and protein expression of iron homeostasis genes such as transferrin receptor (TfR), divalent metal transporter (DMT1), Ferroportin (FPN1), and Ferritin (FT) in brain areas associated with memory formation such as the Prefrontal Cortex (PFC), Ventral Tegmental Area (VTA), and hippocampus. Interestingly, we found that 21 day old PAE rats have higher mRNA expression of DMT1 in the PFC, and TfR in the hippocampus, compared to control animals. In contrast FPN has lower mRNA expression in the PFC, and FT and FPN1 have lower expression in the hippocampus. In agreement with these results, we found a 1.5-2 fold increase of TfR and DMT1 protein levels both in the hippocampus and the PFC. Additionally, using an electrophysiological approach, we found that in hippocampal slices from PAE rats, iron treatment decreased long-term potentiation (LTP), but not AMPAR basal transmission (AMPAR fEPSP). In contrast, in control slices Fe-NTA did not affect LTP but decreased significantly the AMPAR fEPSP. Meanwhile, iron chelation with deferiprone decreased AMPAR transmission in PAE and control slices and decreased LTP only in controls slices. These results suggest that PAE affects iron homeostasis of specific brain areas -PFC and hippocampus-, which could be involved in maladaptive cognition observed in this animal model.